A virtù e o bom governo em O Príncipe de Maquiavel - Silva, Adriana Maria da (2013)
This research has as a central issue to comprehend the meaning applied by Maquiavelli to the virtù s term. The challenge of this work is to uncover the true cause of the success of political attitudes, in other words, to reveal as a concept virtù relates to the behaviour of men who lead the politics, a behaviour that its qualities determine the positive or negative results of the politic actions to whom governs it, regardless of their personal or religious virtues. Finding results and extracting lessons, knowledge and examples to be followed, Maquiavelli offers perspectives to the ways of acting in the political scenery. Virtù constitutes and becomes effective only with the fortune participation, that is why the objective of our exposition will be to analyze the relashion between determination and indetermination that exists between this two polos that dominate the art of governing.